2011
DOI: 10.1007/jhep09(2011)093
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in Hawking radiation and the infall problem

Abstract: It is sometimes believed that small quantum gravity effects can encode information as 'delicate correlations' in Hawking radiation, thus saving unitarity while maintaining a semiclassical horizon. A recently derived inequality showed that this belief is incorrect: one must have order unity corrections to low energy evolution at the horizon (i.e. fuzzballs) to remove entanglement between radiation and the hole. In this paper we take several models of 'small corrections' and compute the entanglement entropy nume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 76 publications
2
105
0
Order By: Relevance
“…Even though the answer to this was not clear, the expression (4.2) was generally accepted as holding for Rindler horizons, and in particular was used to 'derive' Einstein's equation from thermodynamics [42]. What we will now see is that in terms of fuzzballs, there is a logical explanation of (4.2) as a count of states, even though we are describing the Rindler quadrants of empty Minkowski space [43].…”
Section: The Entropy Of Rindler Spacementioning
confidence: 99%
“…Even though the answer to this was not clear, the expression (4.2) was generally accepted as holding for Rindler horizons, and in particular was used to 'derive' Einstein's equation from thermodynamics [42]. What we will now see is that in terms of fuzzballs, there is a logical explanation of (4.2) as a count of states, even though we are describing the Rindler quadrants of empty Minkowski space [43].…”
Section: The Entropy Of Rindler Spacementioning
confidence: 99%
“…Thus, they argue that an infalling observer will experience a firewall (if the assumptions hold). 1 Firewalls were also proposed in a different context in [43], following [44][45][46][47][48][49][50][51][52][53]. There, in the nonperturbative setting of AdS/CFT, it was argued that the existence of any spacetime at all behind a general horizon (including Rindler horizons in pure AdS) requires entanglement between the degrees of freedom associated with the region outside the horizon and some other independent degrees of freedom (see figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mathur introduced fuzzball complementarity [16]: while quanta with E ∼ T H do not have free infall independent of the details of the fuzzball, more energetic quanta E T H fall in freely, oblivious to the details of the fuzzball. This proposal, further developed in [6,17,23,24], explains in what sense black holes are coarse-grained descriptions of fuzzballs. We review fuzzball complementarity in section 3.…”
Section: Jhep09(2013)012mentioning
confidence: 97%
“…If black hole evaporation were unitary then a black hole in a typical state would evaporate according to figure 1a. In a recent series of papers [15][16][17][18][19], however, Mathur showed that for black hole evaporation with only small corrections to the leadingorder Hawking process the von Neumann entropy of radiation keeps monotonically increasing in time with no turnover, as shown in figure 1b. To get an evolution as in figure 1a, he therefore argues that the small correction have to be made large and we can no longer trust effective field theory at the horizon scale.…”
Section: Jhep09(2013)012mentioning
confidence: 99%
See 1 more Smart Citation